Influence of Climate Change Tax Strategies on Willingness to Pay in Asia and Europe - Neeranat K. Rakangthong; Somjintana Koompai; Shubham Pathak; Qin Zhu (Journal of Human, Earth, and Future)
Previous research has demonstrated that people's reluctance to pay taxes to mitigate climate change stems from their belief in the tax system, its transparency and fairness, and its ability to distribute income equally and inclusively. This issue stems from the fact that people in different countries lack financial support to address climate change. This study aims to compare this willingness to pay taxes and to find strategies for organizing taxes to make people more willing to pay them by emphasizing the significant role of cultural values ​​between Asian and European countries, following the model of Inglehart and Welzel. This research adopts a quantitative methodology using secondary data from the European Investment Bank (EIB), which conducted a global public opinion survey in 2023–2024. The data was analyzed using ANOVA and stepwise multiple regression analysis. The results show that Asian countries with traditional and survival values ​​are more willing to pay taxes than those with secular and self-expressive values ​​in Europe. The new findings are that tax policies that hold polluters accountable for their carbon emissions, or fossil tax reforms, are most acceptable in countries with different values ​​in Asia and Europe. This research paves the way for sustainable tax reforms.